Recovery from Financial Crises: Evidence from 100 Episodes - Reinhart, Carmen M.; Rogoff, Kenneth S. (American Economic Review, 2014)
We examine the evolution of real per capita GDP around 100 systemic banking crises. Part of the costs of these crises owes to the protracted nature of recovery. On average, it takes about 8 years to reach the pre-crisis level of income; the median is about 6.5 years. Five to six years after the onset of crisis, only Germany and the United States (out of 12 systemic cases) have reached their 2007-2008 peaks in real income. Forty-five percent of the episodes recorded double dips. Post-war business cycles are not the relevant comparator for the recent crises in advanced economies.